Physical activity promotion through digital technology among older adults with type 2 diabetes mellitus: A scoping review - Tina Agnes, MPT; Ullas U. Nayak, MPT; Muralidhar M. Kulakarni, MD; G. Arun Maiya, PhD (Journal of Taibah University Medical Sciences)
الملخص: أهداف البحث: تتطور التقنيات الرقمية بسرعة في مجال الرعاية الصحية، مع إمكانية تعزيز تقديم الخدمات في العيادات الخارجية والداخلية والمجتمعية، مما يؤدي في النهاية إلى تحسين ممارسات الرعاية الصحية. وقد ثبت أنها واحدة من أكثر البدائل أمانا للزيارات الشخصية للأفراد المعرضين للخطر وأولئك المحصورين في منازلهم، وبالتالي تقليل السفر وتسهيل التواصل بين مقدمي الرعاية الصحية. تهدف هذه المراجعة إلى فهم تطبيق التكنولوجيا الرقمية في تعزيز النشاط البدني والتمارين الرياضية لدى كبار السن المصابين بداء السكري من النوع 2. طريقة البحث: تم اتباع منهجية مراجعة شاملة لتحديد النطاق باستخدام إطار العمل المكون من ست خطوات الذي طوره أركسي وأومالي. تم إجراء بحث في ست قواعد بيانات: سكوبس، وإمباس، وبوب ميد، وبروكويست، وويب أوف ساينس، والفهرس التراكمي لأدبيات التمريض والصحة المتحالفة، وتم استرداد سبع دراسات. النتائج: شمل البحث من ست قواعد بيانات 3252 سجلا. ولم تستوف سوى سبع وثائق معايير الاختيار النهائية وتم تضمينها في مراجعتنا. وقد نشأت جميع الدراسات السبع في بلدان ذات دخل مرتفع. ولم تذكر سوى دراسة واحدة من الدراسات السبع استخدام بروتوكول مفصل للتمرين. الاستنتاجات: تعتبر التكنولوجيا الرقمية من حيث الهواتف الذكية حلا فعالا ومجديا لتقديم برامج تعزيز النشاط البدني لكبار السن المصابين بمرض السكري من النوع 2 ويمكنها تحسين النتائج المتعلقة بالصحة. Abstract: Objectives: Digital technologies in healthcare are rapidly advancing, and have the potential to enhance delivery across outpatient, inpatient, and community settings, thus ultimately improving healthcare practices. These technologies have been demonstrated to be among the safest alternatives to in-person visits for vulnerable or homebound people, thereby avoiding travel and facilitating healthcare-provider communication. This review was aimed at understanding the application of digital technology to promote physical activity and exercise in older adults with type 2 diabetes mellitus. Methods: A comprehensive scoping review method was followed, according to the six-step framework developed by Arksey and O'Malley. A search was performed in six databases: Scopus, Embase, PubMed, ProQuest, Web of Science, and the Cumulated Index to Nursing and Allied Health Literature (CINAHL). Seven studies were retrieved. Results: The search in the six databases returned 3252 records, only seven of which met the final selection criteria and were included in the review. All seven studies were conducted in high-income countries. Only one of the seven studies reported using a detailed exercise protocol. Conclusion: Digital technology using smartphones provides an effective and a feasible solution to deliver physical activity promotion programs to older adults with type 2 diabetes mellitus, and can improve heath related outcomes.